2017
DOI: 10.1002/aic.15787
|View full text |Cite
|
Sign up to set email alerts
|

Capillary driven flow in wettability altered microchannel

Abstract: The capillary driven flow of water inside a microchannel with altered wettabilities is experimentally investigated and modeled theoretically. The surfaces of the PDMS made microchannel are exposed to oxygen plasma, rendering the surfaces increasingly hydrophilic, which provides the driving force for the flow. The plasma treated surfaces are characterized using topography and phase imaging of AFM scanning, as well as nano‐indentation, to correlate the distinct structural changes to the hydrodynamic profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Gogolides and co‐workers reported the preparation of microchannels with capillary filling performance by oxygen plasma etching, and further provided the microchannel with hydrophobic valving performance by C 4 F 8 plasma treatment . DasGupta and co‐workers functionalized the PDMS microchannels by oxygen plasma treatment . The functional microchannels were prepared by irreversible bonding of oxygen plasma treated PDMS mold and PDMS‐coated glass substrate.…”
Section: Inner Surface Design Of Microchannelsmentioning
confidence: 99%
“…Gogolides and co‐workers reported the preparation of microchannels with capillary filling performance by oxygen plasma etching, and further provided the microchannel with hydrophobic valving performance by C 4 F 8 plasma treatment . DasGupta and co‐workers functionalized the PDMS microchannels by oxygen plasma treatment . The functional microchannels were prepared by irreversible bonding of oxygen plasma treated PDMS mold and PDMS‐coated glass substrate.…”
Section: Inner Surface Design Of Microchannelsmentioning
confidence: 99%
“…Understanding the multiphase transport process in microfractures or microchannels is crucial to predict production performance in shale gas reservoirs [1][2][3] as well as control fluid transport in microfluidic devices. 4,5 Gas shale is a complex sedimentary system that is considered to exhibit different storage space types 6,7 and complex fluid transport properties. 8,9 It is widely observed that not only confined nanopores but also microfractures extensively exist as shown in Figure 1, [10][11][12] which are often regarded as preferential transport pathways in shale gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the multiphase transport process in microfractures or microchannels is crucial to predict production performance in shale gas reservoirs 1‐3 as well as control fluid transport in microfluidic devices 4,5 . Gas shale is a complex sedimentary system that is considered to exhibit different storage space types 6,7 and complex fluid transport properties 8,9 .…”
Section: Introductionmentioning
confidence: 99%